Balinese Arak as Substitute of Imported Spirits and Liqueurs in The Process of Making Dadar Gulung Flambe - Massenga, Lidjah Magdalena; Arcana, I Nyoman; Wiratnaya, I Nyoman (Jurnal Ilmiah Hospitality Management, 2023)
Making Dadar Gulung Flambe by using Arak Bali drink as a substitute for imported spirits and liqueurs such as French Brandy or Jamaican Rum is one alternative to reduce the cost of food so that the selling price of this dish can be more affordable and will increase the use of local Balinese products as products sold in hotels and restaurants. The purpose of this study was to analyze the level of liking for Dadar Gulung Flambe dishes that use Balinese Arak as a substitute for imported spirits and liqueurs. This study uses qualitative data. The quantitative data in this study is the result of data processing from distributing hedonic test. The data analysis technique used in this final project research is a quantitative descriptive data analysis technique. Through the Hedonic Test by distributing hedonic test questionnaires to 15 panelists using four assessment indicators, such as Taste, Aroma, Color and Texture. The results of this study showed that the average level of preference of panelists for Dadar Gulung Flambe who used Balinese Arak drink as a substitute for imported spirits and liqueurs was 4.3 in the Very Like category.